Supernatural Power in William Shakespeare’s the Tempest - Efrizah, D (KnE Social Sciences, 2018)
This paper analyzes about supernatural power which is found in the Drama The Tempest. It is a play comedy or romance works written by William Shakespeare around the year 1610-1611 which is one of Shakespeare’s best works. There are some protagonist characters in The Tempest who use supernatural power to defeat their enemies for a purpose. It is absolutely full of magic. Prospero is the main character who uses magic as a supernatural force to regain his position as Duke of Milan. However, he is helped by his fairy servant, Ariel, throughout the play, whom he saved and liberated from a cloven pine tree by using his magic and supported by some other spirits. There are several theories of supernatural including magic given by Marcel Mauss who describes about magic. Magic is one of supernatural power which is very useful in Prospero’s life as the protagonist person in the story of Drama The Tempest. Keywords: supernatural; power, magic.